2017
DOI: 10.1016/j.bjpt.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of musculoskeletal symptoms in a manufacturing company in Brazil: a cross-sectional study

Abstract: HighlightsUpper limb MSD were prevalent among manual manufacturing workers.Shoulder was the body region with the highest prevalence of symptoms.Repetitive work and lack of rest breaks are influential risk factors for MSD.Performing work pause was identified as a significant variable.MSD had a significant negative impact on workers’ general health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 34 publications
(60 reference statements)
6
9
0
2
Order By: Relevance
“…diagnoses) at the elbow, forearm and/or wrist were found in 56% (39/70), of which 12/20 (70%) grinders, 14/24 (54%) packers and 13/26 (42%) control persons. These results are consistent with previous studies showing a prevalence rate of symptoms between 21% and 71% in the study group and between 6% and 50% in the control group [34][35][36][37][38][39][40][41][42][43][44][45][46]. With regard to diagnoses, existing studies report a prevalence between 21% and 56% in the study group compared to 5-22% in the control group [35,36,38,39,40,42].…”
Section: Discussionsupporting
confidence: 92%
“…diagnoses) at the elbow, forearm and/or wrist were found in 56% (39/70), of which 12/20 (70%) grinders, 14/24 (54%) packers and 13/26 (42%) control persons. These results are consistent with previous studies showing a prevalence rate of symptoms between 21% and 71% in the study group and between 6% and 50% in the control group [34][35][36][37][38][39][40][41][42][43][44][45][46]. With regard to diagnoses, existing studies report a prevalence between 21% and 56% in the study group compared to 5-22% in the control group [35,36,38,39,40,42].…”
Section: Discussionsupporting
confidence: 92%
“…The respondents do not do heavy work (70%) and play sport (70%), which showed that all the respondents are physically healthy and have had enough sleep. This was supported by the previous study done by Hembecker, Reis, Konrath, Gontijo, and Merino (2017), who stated that sleep disorders could indicate another musculoskeletal problem among the workers. The reduced amount of sleep can cause a lot of tiredness and can lead to muscle discomfort and fatigue.…”
Section: Discussionsupporting
confidence: 81%
“…The design of our cross-sectional study with a control group, physical examination of the subjects, and the use of a questionnaire can be found in several studies related to different industries. Our literature research showed a prevalence of upper extremity pain (i.e., symptoms) of between 21% and 71% in the study group and between 6% and 50% in the control group [56][57][58][59][60][61][62][63][64][65][66][67][68]. This is in line with our investigation where symptoms were reported in the first questionnaire by 8/20 (40%) grinders, 14/24 (58%) packers, and 11/26 (42%) people in the control group.…”
Section: Prevalence Of Symptoms and Diagnosessupporting
confidence: 90%